Episiotomy and associated complications: A literature review (Research, Society and Development, 2024)
Introduction: Episiotomy consists of a perineal surgical incision, the region located between the woman's vagina and anus. The practice can be classified according to the location in which it is done: median, medio-lateral or lateral. The median incision consists of a cut made vertically from the labia minora towards the rectum; on the mediolateral side, a cut is made diagonally from the hymenal ring. The lateral technique is no longer used, as it causes more bleeding and injuries. Objective: This study aims to evaluate the relationship between parity and episiotomy and the complications associated with this practice. Methods: This is a systematic literature review about episiotomy and the complications associated with its practice. A bibliographic survey was carried out through electronic searches in the following databases: Scientific Eletronic Library Online (SciELO), National Library of Medicine (PubMed) e Literatura Latino Americana em Ciências da Saúde (LILACS), from 2019 to 2023 The following descriptors were used: Episiotomy, Pregnancy, Normal Birth. Results and Discussion: In most of the articles analyzed, the main indications for episiotomy were: primiparous women, young maternal age, newborn weight greater than 4,000 grams, shoulder dystocia, newborn with fetal macrosomia and fetus with abnormal cardiac function. Conclusion: It is therefore clarified that today episiotomy is still adopted as a routine procedure, contradicting the evidence that invalidates the indications for this practice, as it exceeds the rates recommended by the World Health Organization (WHO), being carried out without criteria.